Papel de la auditoría forense frente a la corrupción generada en la emergencia sanitaria (COVID-19) (2020)
The field of Forensic Audit provides investigative and judicial inputs, since they are consolidated as sufficient and effective evidence to clarify facts of economic crimes before the courts and also to avoid them. Consequently, techniques and tools are currently being applied to determine trends and impacts on the potential for corruption in the public sector; since the modus operandi of the new criminality in the world is transversal in terms of new technologies, administrative disloyalty and, mainly, it is exercised with impunity in high positions of the State.